Successful Infection of Tick Cell Cultures of Rhipicephalus sanguineus (Tropical Lineage) with Ehrlichia canis - Barros-Battesti, Darci Moraes [UNESP]; Machado, Rosangela Zacarias [UNESP]; Andre, Marcos Rogerio [UNESP]; Marques de Sousa, Keyla Carstens [UNESP]; Franze, Daniella Aparecida; Lima-Duarte, Leidiane; Cirelli-Moraes, Angelina; Nunes, Pablo Henrique; Labruna, Marcelo Bahia; Moraes-Filho, Jonas; Martins, Maria Marlene; Juan Szabo, Matias Pablo (Mary Ann Liebert, Inc, 2018)
There are two distinct lineages of ticks, Rhipicephalus sanguineus, in South America: tropical and temperate lineages. Only the tropical lineage is recognized as competent vector for Ehrlichia canis. The epidemiological data of canine monocytic ehrlichiosis is congruent with the distribution of the two lineages of R. sanguineus. Herein, we report the infection of R. sanguineus (tropical lineage) cell cultures with E. canis, after cryopreservation. R. sanguineus (tropical lineage) cell identity was confirmed by sequencing using a 16S rDNA gene fragment. Tick cell cultures were prepared in L-15B medium supplemented with 10%, 15%, and 20% Fetal Bovine Serum (FBS), and 10% of Tryptose Phosphate Broth (TPB). Cell cultures developed better at the concentration of 20% of FBS. Cultures in the fifth harvest (approximately 7 months later) were selected for the first infections. Optimal R. sanguineus cell growth and adhesion was observed (5.0x10(6) cells/mL, and the population doubling time every 57h). Once infected with E. canis, the cultures were maintained in L-15B medium supplemented with 2% and 5% of FBS fortified with iron and 10% TPB. Infected cells were also cryopreserved. DNA was extracted from infected and noninfected cells and analyzed using quantitative real-time PCR targeting the E. canis-dsb gene. Primary culture of the fifth passage was infected by E. canis and it maintained the pathogen for at least 40 days before partial cell destruction. Subcultures of infected cells (fresh and cryopreserved cultures) onto new tick cell cultures were successful. The E. canis infection was confirmed by real-time PCR and light and transmission electron microscopy. The R. sanguineus (tropical lineage) cells infected with E. canis successfully infected new tick cell cultures, showing that these cells could be an alternative substrate for maintenance of this pathogen.
Keywords: brown dog tick; tropical lineage; tick cell culture; Ehrlichia canis